Phase singularity reduction in speckle interferometry by tailoring the spatial coherence of light - Mantel, K.; Barakat, Ismail; Nercissian, Vanusch; Harder, I.; Rothau, S. (Applied Optics, 2021)
Reducing the number of phase singularities in speckle interferometry by physical means increases the quality of the phase deconvolution and enhances the separability of fringe systems, especially for highly dynamic fringe systems. The reduction is achieved by tailoring the spatial coherence of the light source at the entrance of the interferometer. The reduction mechanism is non-intuitive and rests on a change of size and of position of the speckle patterns as a result of the spatially shaped coherence. After demonstrating the amount of reduction that may be achieved, the reduction mechanism is explained theoretically and via simulations, and it is vindicated in an experiment using a Michelson-Mach-Zehnder interferometer hybrid.
CRIS-Team Scopus Importer:2021-08-20